2014
DOI: 10.3758/s13414-014-0762-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual failures in the selection and identification of low-prevalence targets in relative prevalence visual search

Abstract: Previous research has shown that during visual search tasks target prevalence (the proportion of trials in which a target appears) influences both the probability that a target will be detected, and the speed at which participants will quit searching and provide an 'absent' response. When prevalence is low (e.g., target presented on 2 % of trials), participants are less likely to detect the target than when prevalence is higher (e.g., 50 % of trials). In the present set of experiments, we examined perceptual f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(121 citation statements)
references
References 21 publications
13
108
0
Order By: Relevance
“…Driving requires continual and rapid decision-making and makes significant cognitive demands of the motorist, who must detect, recognise, predict, and respond to a variety of stationary and moving objects, in a range of sizes, in a highly dynamic environment. Furthermore, drivers must not just select targets for their attention; they must continuously identify the most important target for their driving task 20. In short, driving demands a tremendous amount of visual and cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…Driving requires continual and rapid decision-making and makes significant cognitive demands of the motorist, who must detect, recognise, predict, and respond to a variety of stationary and moving objects, in a range of sizes, in a highly dynamic environment. Furthermore, drivers must not just select targets for their attention; they must continuously identify the most important target for their driving task 20. In short, driving demands a tremendous amount of visual and cognitive processing.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our results can also help to offer new insights into how participants fail to detect targets in visual search. It has been noted that targets are often missed as a consequence of failures of perceptual identification (Cain et al., ; Schwark et al., )—that is, even after fixating the target object, the target is still missed by participants (Engel, ; Godwin et al., ,a,b; Godwin et al., ; Gould & Cairn, ; Hooge & Erkelens, ; Hout, Walenchok, Goldinger, & Wolfe, ; Nodine & Kundel, ). These failures have important societal consequences, such as in radiographic image screening, where tumors can go undetected and missed by searchers.…”
Section: Discussionmentioning
confidence: 99%
“…The existence of perceptual identification errors has been used as evidence against strict direct‐control accounts, with such occurrences being regarded as a natural by‐product of the fact that fixations can be terminated by an indirect mechanism (e.g., an autonomous timer) that drives fixations to new locations irrespective of whether or not the processing of an object at a given fixation location has been completed. However, more recent studies (Godwin, Menneer, Riggs, Cave, & Donnelly, ; Godwin et al., ; Hout et al., ) have found that perceptual identification errors are more likely to occur when the target is presented on a small proportion of trials (5% of trials) compared with a higher proportion of trials (45%), perhaps because of priming from target repetition and/or expectations about the likelihood of a target being presented (Godwin et al., ,b). This finding suggests that failures to detect the target upon fixating it may reflect object identification failures rather than being a consequence of some indirect mechanism, as predicted by indirect‐control accounts.…”
Section: A New Approach: Using Lag‐2 Revisits To Understand Trade‐offmentioning
confidence: 99%
See 1 more Smart Citation
“…Both information-sampling and decision-making are vital components in the detection of visual targets. When information-sampling fails to guide the eyes to targets, those targets are often missed (Chapman & Underwood, 1998;Godwin, Menneer, Riggs, Cave, & Donnelly, 2015;Kundel & Nodine, 1975;Nodine & Mello-Thoms, 2000). When the targets are examined, decision-making can also fail to detect the targets once fixed, causing the targets to again be missed (Cain, Adamo, & Mitroff, 2013;Godwin et al, 2015;Nodine & Kundel, 1987;Schwark, MacDonald, Sandry, & Dolgov, 2013).…”
mentioning
confidence: 99%